COMPARISON PERFORMANCE OF INDUCTION MOTOR USING SVPWM AND HYSTERESIS CURRENT CONTROLLER - Sulaiman , Marizan; Ibrahim, Zulkifilie; Patakor, Fizatul Aini (Little Lion Scientific Islamabad Pakistan, 2011)
This paper presents the comparative performances of three phase induction motors using space vector pulse width modulation (SVPWM) and hysteresis current controller. An indirect field orientation is applied to ensure decoupling control between torque and flux of the induction motor. The hysteresis current controller is built in with PI speed controller and three hysteresis current bands while the SVPWM system is embedded with the two control loops, the inner current control loop and the outer speed control loop using PI controller. Both systems were run and tested using MATLAB/SIMULINK software. The simulation results demonstrate that the SVPWM can improve the quality of the stator current and reduce the torque ripple while maintaining the other performance characteristics of the system.